An update on the epidemiological situation of spotted fever in Brazil. Issue 1 (December 2016) - de Oliveira, Stefan; Guimarães, Jessica; Reckziegel, Guilherme; Neves, Bidiah; Araújo-Vilges, Keline; Fonseca, Lidsy; Pinna, Fernanda; Pereira, Simone; de Caldas, Eduardo; Gazeta, Gilberto; Gurgel-Gonçalves, Rodrigo
Abstract Background Spotted fever is a tick-borne rickettsial disease. In Brazil, its notification to the Ministry of Health is compulsory. Since 2007, cases of spotted fever have been integrated to the Notifiable Diseases Information System, and epidemiological analyzes are part of the routines on surveillance programs. Methods This descriptive study updates epidemiological information on cases of spotted fever registered in Brazil between 2007 and 2015. Results In Brazil, 17, 117 suspected cases of the disease were reported and 1, 245 were confirmed in 12 states, mainly in São Paulo (550, 44.2 %) and Santa Catarina (276, 22.2 %). No geographic information was registered for 132 cases (10.6 %). Most of the infected people were men (70.9 %), mainly in rural areas (539, 43.3 %), who had contact with ticks (72.7 %). A higher number of suspected cases were registered between 2011 and 2015, but the number of confirmed cases and the incidence were relatively low. Moreover, 411 deaths were registered between 2007 and 2015, mainly in the southeastern region of the country, where the case-fatality rate was 55 %. Lack of proper filling of important fields of notification forms was also observed. Conclusions The results showed expansion of suspected cases of spotted fever and high case-fatality rates, which could be related to diagnostic difficulties and lack of prompt treatment. These factors may comprise limitations to the epidemiological surveillance system in Brazil, hence improvement of notification and investigation are crucial to reduce morbidity and mortality due to spotted fever in Brazil.